Effects of programmed physical activity on body composition in post‐pubertal schoolchildren - Edson dos Santos Farias; Ezequiel Moreira Gonçalves; André Moreno Morcillo; Gil Guerra‐Júnior; Olga Maria Silverio Amancio (Brazilian Society of Pediatrics, 2015)
Objective: To assess body composition modifications in post‐pubertal schoolchildren after practice of a physical activity program during one school year. Methods: The sample consisted of 386 students aged between 15 and 17 years and divided into two groups: the study group (SG) comprised 195 students and the control group (CG), 191. The SG was submitted to a physical activity program and the CG attended conventional physical education classes. Body composition was assessed using body mass index (BMI), percentage of body fat (%BF), fat mass (FM), and lean mass (LM). Results: A positive effect of the physical activity program on body composition in the SG (p < 0.001) was observed, as well as on the interaction time x group in all the variables analyzed in both genders. A reduction in %BF (mean of differences = -5.58%) and waist circumference (-2.33 cm), as well as an increase in LM (+2.05 kg) were observed in the SG for both genders, whereas the opposite was observed in the CG. Conclusion: The practice of programmed physical activity promotes significant reduction of body fat in post‐pubertal schoolchildren.